Engineering lecturers’ perceptions towards student self- assessment in enhancing undergraduates’ oral presentation skills - Abdelmadjid, Benraghda; Noor Raha, Mohd Radzuan (Universiti Malaysia Pahang, 2019)
In recent years, self-assessment has been increasingly implemented as an alternative method of assessment in tertiary educational contexts. The research described in this paper employed semi-structured interviews as an instrument to evaluate engineering lecturers’ perceptions towards student self-assessment in developing their non-verbal communication skills in technical oral presentations. A sample of 10 engineering lecturers from a technical university participated in the study. Semi-structured interview data revealed that most engineering lecturers viewed student self-assessment positively and they reported on student self-assessment as providing learning values, because the latter viewed student self- assessment as a learning aid. The results further showed that student self-assessment could promote the students’ learning, an increase of students’ willingness to deliver oral presentations, and self-enabling. Therefore, student self-assessment can be a powerful method to increase learning by raising the awareness about the necessity of non-verbal communication skills in delivering technical oral presentations.